2022
DOI: 10.1111/jgs.18054
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported geriatric assessment‐based frailty index among older adults with gastrointestinal malignancies

Abstract: Background Older adults with cancer are at increased risk of treatment‐related toxicities and excess mortality. We evaluated whether a patient‐reported geriatric assessment (GA) based frailty index can identify those at risk of adverse outcomes. Methods Older adults (≥60 years) enrolled in a single‐institutional prospective registry underwent patient‐reported GA at initial evaluation in our medical oncology clinic. Using deficit accumulation method, we constructed a 44‐item frailty index (CARE‐FI), categorizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Once the GA is completed, the results can be used to identify individual domain impairments, calculate a summary score of overall frailty, [19][20][21] and calculate the risk of severe chemotherapy toxicities (see ASCO videos). For treatment decision making, it can be very helpful to integrate the risk of adverse outcomes and/or severe chemotherapy toxicities on the basis of the GA results to inform a conversation about the risks/benefits of cancer treatments for individual patients.…”
Section: Question 4: How Should I Use the Ga Results To Guide Managem...mentioning
confidence: 99%
“…Once the GA is completed, the results can be used to identify individual domain impairments, calculate a summary score of overall frailty, [19][20][21] and calculate the risk of severe chemotherapy toxicities (see ASCO videos). For treatment decision making, it can be very helpful to integrate the risk of adverse outcomes and/or severe chemotherapy toxicities on the basis of the GA results to inform a conversation about the risks/benefits of cancer treatments for individual patients.…”
Section: Question 4: How Should I Use the Ga Results To Guide Managem...mentioning
confidence: 99%
“…Using the principles of deficit accumulation and following the procedures outlined by Searle et al, 24 we constructed the CARE Frailty Index 25 . Based on 44 identified health deficits from the CARE geriatric assessment tool, the CARE Frailty Index was calculated as the proportion of deficits for each patient (range 0–1).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were required to have nonmissing data for at least 30 items in order to compute a valid frailty score and were categorized as robust (0–0.2), prefrail (0.2–0.35), and frail (>0.35), as previously described 24 . Our team has previously shown that the CARE frailty index predicts functional decline, severe chemotherapy toxicities, and survival among older adults; 25 similarly constructed frailty indices have shown comparable results 12–15,26 . See Table S1 for a full list of the CARE frailty index items.…”
Section: Methodsmentioning
confidence: 99%
“…26 Detailed methodology for calculating the CARE FI is described elsewhere and in Table S2. 11,27 Briefly, each item queried the presence or absence of a health deficit across GA domains and was scored as 0 (absence of deficit), 0.5 (intermediate response [e.g. sometimes/ maybe]), or 1 (presence of deficit).…”
Section: Outcomementioning
confidence: 99%
“…9 Frailty can also increase the risk for treatment toxicity, reduced health-related quality of life, institutionalization, and mortality. [9][10][11][12] Therefore, whereas the relative effect of frailty in older adults with cancer is similar to that without cancer, the cumulative effect becomes greater in those with cancer.…”
Section: Introductionmentioning
confidence: 99%